How much of the real-world laboratory is hidden in current transdisciplinary research? - Rogga, Sebastian; Zscheischler, Jana; Gaasch, Nadin (Oekom, 2018)
The concept of real-world laboratories is difficult to distinguish from the concept of transdisciplinary research. Thus, the question has arisen: to what extent is the real-world laboratory truly novel? If transdisciplinary research is considered a process providing only socially robust knowledge and orientation (instead of solutions), then the real-world lab could be thought of as a model in which evidence-supported solutions can be tested and adjusted, and progress can be achieved.
Keywords: Nachhaltige Entwicklung; Forschungsmethode; Wissenstransfer; Reallabor; Transdisziplinarität; Nachhaltigkeitsforschung